Microstructural properties of ZnO epitaxial films grown on p-InP(100) substrates at low temperature - Kim, TW; Yoon, YS (ELSEVIER SCIENCE BV, 2000)
ZnO thin films were grown on p-InP(100) substrates by using radio-frequency magnetron sputtering at low temperature (similar to 200 degrees C). Atomic force microscopy images showed that the root mean square of the average surface roughness of the ZnO film was 17.2 Angstrom, and X-ray diffraction and transmission electron microscopy (TEM) measurements showed that the ZnO film layers grown on the InP substrates were epitaxial films with strong (0 0 0 1) preferential orientation. Anger electron spectroscopy and bright-field TEM measurements showed that the ZnO epitaxial films grown on InP substrates at 200 degrees C had no significant interdiffusion problems. These results indicate that the ZnO epitaxial films grown on p-InP(1 0 0) substrates at low temperature, hold promise for new kinds of potential high-speed optoelectronic devices based on InP substrates, such as low-loss optical waveguides and high-efficiency solar cells and that the ZnO epitaxial films grown on p-InP(1 0 0) substrates can be used as promising buffer layers for the growth of the GaN-related epilayers. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: MOLECULAR-BEAM EPITAXY; THIN-FILMS; SAPPHIRE; GAN; PLANE